YOUTH EMPLOYMENT IN UZBEKISTAN: PROBLEMS AND OPPORTUNITIES: https://doi.org/10.5281/zenodo.14717413 - Sunnatov , Qudratulla (Journal of International science networks, 2024)
Abstract: This article analyzes the problems and opportunities related to youth employment in Uzbekistan. It discusses the position of youth in the labor market, issues in ensuring their employment, such as unemployment, the inadequacy of vocational education, and the quality of job opportunities. It also addresses existing opportunities to increase youth employment, the need to modernize vocational training, encourage entrepreneurship, and create new opportunities in the digital economy. The article suggests effective ways to ensure youth employment and examines the role of the government and future measures to address these issues.